Pengidentifikasian Kualitas Air Laut Terkait Dengan Pengelolaan Limbah Plastik - Telaumbanua, Dara Dwista; Zebua, Ratna Dewi; Telaumbanua, Putra Hidayat (Jurnal Perikanan dan Kelautan, 2024)
The problem of plastic waste in the ocean is a global problem that endangers the quality of sea water and the marine ecosystem as a whole. This article discusses the relationship between how to manage plastic waste and how it affects seawater quality, such as pH, temperature, salinity, dissolved oxygen (DO), and biological oxygen demand (BOD5). Research from the literature shows that plastic waste, especially microplastics and macroplastics, can affect the chemical and physical quality of sea water. For example, a decrease in pH levels due to accumulated organic acids, local heating due to sunlight absorbed by plastic, and changes in salinity due to interaction with fresh water. In addition, the accumulation of plastic causes a reduction in dissolved oxygen (DO) and an increase in BOD5 levels, which is detrimental to marine ecosystems. Decreased water quality can endanger marine species because these species are very dependent on the chemical balance of the water. Despite much research on the impact of plastic waste on water quality, there remains a gap in understanding the long-term impacts and the need for more comprehensive plastic waste management. Further research is needed to resolve these issues and create more effective management strategies.